Digital storytelling - brand narratives in social media (analysis based on the example of the "Vianek" brand) - Chorna, Marta (Linguistic creativity in marketing, 2022)
The article is an attempt to introduce the concept of digital storytelling, which brands are increasingly using in social media. I analyzed the messages of the Polish natural cosmetics company Vianek. The aim of the study is to show how brands use narrative marketing and how to build their narrative around ecology. This analysis concerns posts and stories posted on the Instagram platform and reflect the main topic, which is digital storytelling.